Decreased expression of apelin in placentas from severe pre-eclampsia patients. (November 2013) - Inuzuka, Hiromi; Nishizawa, Haruki; Inagaki, Ayaka; Suzuki, Machiko; Ota, Sayuri; Miyamura, Hironori; Miyazaki, Jun; Sekiya, Takao; Kurahashi, Hiroki; Udagawa, Yasuhiro
<x xml:space="preserve">Abstract</x> Objective: It is well documented that anti-angiogenic factors are likely to play essential roles in the etiology of pre-eclampsia. Apelin is a small peptide that may potentially act as an angiogenic factor. The expression of apelin was examined at the RNA and protein levels in this study. Methods: We compared the expression of apelin, examined using quantitative reverse-transcription polymerase chain reaction, western blotting, enzyme-linked immunosorbent assay and immunostaining, between pre-eclamptic patients and normotensive controls. Results: Apelin messenger RNA is significantly decreased in pre-eclamptic placentas compared with normotensive pregnancies (p < 0.05). Apelin protein levels are also lower in pre-eclamptic placentas than the controls but higher in the maternal circulation in pre-eclampsia patients. Immunohistochemical signals for apelin and its receptor APJ were detected mainly in the cytoplasm of syncytiotrophoblasts in chorionic villi and trophoblast-lineage cells in the decidua of term placentas. In early gestation, stronger APJ signals were observed at the cellular membrane. Conclusions: A functional role of the apelin–APJ system is likely in early gestation, and this raises the possibility that a dysfunctional apelin–APJ system contributes to the onset of pre-eclampsia via decreased angiogenic activity in placental implantation.